Adolescentes com paralisia cerebral: estudo de casos clínicos - Castellano, Giuliana Bonucci (2010)
This dissertation presents the Speech-Language Pathology clinic as a space for listening to the (talking) body of individuals with cerebral palsy. In this manner, the irreversible motor marks on their bodies may prevent them from articulating speech, but do not stop Sabrina and Juan from gaining a voice through the Other s speech. Aim: To study two clinical cases of adolescents with cerebral palsy. Methods: This study presents fragments of Speech-Language Therapy sessions in which the diary and Supplementary and/or Alternative Communication board were used for support. These fragments were analyzed based on the language symptoms organization model, according to (GOUVÊA, FREIRE and DUNKER 2009). This model was set on the multilayered and articulated structure of the strata of writing, speech, language, of the individual, the Other, of the metaphor and the metonym (GOUVÊA, 2007). Results and conclusion: In the presented clinical case studies, it was possible to establish differential diagnoses pertaining to the Speech-Language Pathology clinic, from the outlining of semiology, of the etiogical hypothesis and the consequent (re)direction of Speech-Language therapy based on sanction on the act, the subject and the law